2018
DOI: 10.1159/000485914
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Transplantation of the Internal Limiting Membrane for Refractory Macular Hole following Ruptured Retinal Arterial Macroaneurysm: A Case Report

Abstract: Purpose: To report a case of macular hole (MH) secondary to a retinal arterial macroaneurysm (RAMA) which was successfully treated with an autologous transplantation of internal limiting membrane (ILM). Case Report: An 87-year-old female presented with a sudden decrease in central vision in the right eye. A fundus examination revealed a RAMA in the superonasal macular region, a subretinal hemorrhage (SRH), involving the macula, and a sub-ILM hemorrhage. A pars plana vitrectomy (PPV) was performed. Intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…A similar technique of ILM grafting using double layers of viscoelastic was recently described by Iwakawa et al in a case of refractory MH secondary to ruptured retinal artery macroaneurysm. 7 Our results are comparable to prior studies that utilized free ILM grafting with MH closure rates ranging between 80% to 100% for refractory or very large MHs. [3][4][5] In conclusion, using double layers of viscoelastic facilitates covering and stabilizing the ILM over the MH while reducing the risk of mechanical RPE damage, saving surgical time and potentially promoting anatomical closure.…”
Section: Healiocom/osliretinasupporting
confidence: 84%
“…A similar technique of ILM grafting using double layers of viscoelastic was recently described by Iwakawa et al in a case of refractory MH secondary to ruptured retinal artery macroaneurysm. 7 Our results are comparable to prior studies that utilized free ILM grafting with MH closure rates ranging between 80% to 100% for refractory or very large MHs. [3][4][5] In conclusion, using double layers of viscoelastic facilitates covering and stabilizing the ILM over the MH while reducing the risk of mechanical RPE damage, saving surgical time and potentially promoting anatomical closure.…”
Section: Healiocom/osliretinasupporting
confidence: 84%
“…In recent years, the usefulness of various membrane transplantation techniques such as the inverted ILM flap technique [14][15][16][17], autologous ILM transplantation [18][19][20][21], and the ILM repositioning technique [22,23] for treating intractable macular holes (such as large macular holes, old macular holes, macular holes in eyes with high myopia, and FTMH secondary to SMH due to RAM rupture) has been reported. In a previous study on membrane transplantation for FTMH secondary to RAM rupture, Iwakawa et al reported that autologous ILM transplantation in a patient with FTMH secondary to RAM rupture resulted in successful FTMH closure [24]. Kawaji et al reported three cases in which the ILM repositioning technique was useful [22].…”
Section: Discussionmentioning
confidence: 99%
“…Initially developed to deal with large macular holes the inverted flap technique tends to be used more often to treat large, old and myopic macular holes and for reoperations after conventional surgery has failed. However, it has also been adopted to treat routine small cases and has successfully resolved macular hole with retinitis pigmentosa, in an eye with Coat's Disease, (both unpublished) and a case of secondary rupture of a retinal arterial macroaneurysm 16 , as well as to successfully treat persistent macular hole after retinal detachment surgery, macular holes with AMD, traumatic macular holes, diabetic macular holes, macular holes secondary to uveitis and optic pit maculopathy. SD and SS OCT show foveal microstructure recovery following surgery with the inverted flap technique.…”
Section: Inverted Ilm Flap Techniquementioning
confidence: 99%